Improving the Efficiency of Earth Monitoring Missions by Equipping Small Spacecraft AIST-2 with Electric Propulsion. (2017) - Salmin, V.V.; Tkachenko, S.I.; Volotsuev, V.V.; Kaurov, I.V.
Abstract: The paper considers the problem of equipping a small spacecraft (SS) of the AIST-2 series with electric propulsion for orbital plane maneuvers, such as station keeping and attitude control. Solution of this problem will increase the satellite's operational service life on a low-Earth orbit and, in future, allow attitude control of a satellite constellation.